PENGAWASAN DAN AKUNTABILITAS APARATUR DALAM PERSPEKTIF ETIKA BIROKRASI: STUDI KASUS PADA PEMERINTAH DAERAH KABUPATEN CIANJUR - Iwan Satibi (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2017)
This article aims to find out the problems of supervision and accountability, as well as the strategy of the Cianjur Regency Government in carrying out supervision and accountability in ethical perspectives. This research was conducted using descriptive methods with a qualitative approach. The ethical perspective on supervision and public accountability within the Cianjur Regency Government is actually an